"Subjects" in and of Research: Decolonizing Oppressive Rhetorical Practices in Technical Communication Research. (April 2021) - Agboka, Godwin Y.
Despite the recent surge in social justice and decolonial scholarship, technical and professional communication (TPC) research remains a potential site of oppression. This article is meant to be a call to action; it attempts to (re)ignite discussions about what we value and how we express what we value. It encourages the field of TPC to be more responsive to the experiences and struggles of research participants—those we engage during our knowledge production process. I explore what I call oppressive rhetoric in TPC research with a specific focus on the term subjects in institutional review board forms and in the reporting of some TPC research about research participants. I assert that in spite of our best efforts in advancing the goals of marginalized groups and despite the forward-looking trajectory of progressive research, more work needs to be done to address oppressive rhetoric in TPC scholarship.